PEMANFAATAN CITRA LANDSAT 8 UNTUK ANALISIS PENGARUH DEFORESTASI HUTAN JATI TERHADAP TINGKAT KEKERINGAN LAHAN DI KABUPATEN BLORA TAHUN 2013 – 2021 - Fabian Gery; Pipit Wijayanti; Gentur Adi Tjahjono (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2022)
This research is conducted to: (1) Analyze teak forest deforestation with land cover and forest density parameter in Blora regency on 2013 – 2021. (2) Analyze the land drought level in Blora Regency with TVDI analysis on 2013 – 2021. (3) Analyze the influence of teak forest deforestation towards land drought level in Blora regency. Quantitative – correlative research method is implemented, with spatial approach. The data analysis technique used are (1) Supervised classification and NDVI analysis, (2) TVDI analysis, and (3) correlation with linear regression analysis. The results show that: (1) In 2013 – 2021, there is reduction of teak forest up to 30.000 hectares in Blora regency, with 13.000 hectares forest density was decreased; (2) There are escalations of TVDI value in 2013 – 2021 period, mainly from Rather Wet to Dry drought level, made up to 20.000 hectares in each period; (3) There is an influence from deforestation towards land drought that is showed by the TVDI increase after deforestation occurred in that area, also the correlation value is between 0,3 – 0,7 with significance F value is below 0,05.